Implementation of Indirect Contact Services for National Health Insurance Participants: A Case Study of Jambi City's Primary Healthcare Facilities - Mauliana, Resty; Misnaniarti, Misnaniarti; Syakurah, Rizma Adlia (Journal of Health Policy and Management, 2024)
Background: In response to the COVID-19 pandemic, BPJS Kesehatan has introduced an indirect contact program, but many districts and cities, including Jambi City in Jambi Province, have not achieved the target contact rate. This study aims to analyze the implementation of indirect contact services for JKN participants in Jambi City's primary healthcare facilities (PHC). Subjects and Method: This descriptive qualitative research was conducted at BPJS Kesehatan and PHC Jambi City from March to April 2022. Data were collected through in-depth interviews, observation, and document review. Informants were selected using a consecutive sampling technique based on the type of PHC, including community health centres (Puskesmas), private clinics, and individual practitioners (DPPs), representing the lowest and highest achievement levels. Thematic analysis techniques were used to analyze the data. Results: The findings revealed that the implementation of indirect contact services for JKN participants in Jambi City's PHC was influenced by various factors. These factors included challenges in increasing contact rates, dissatisfaction among JKN participants, and economic constraints faced by the participants. Contributing factors to these challenges was the absence of input guidelines, standard operating procedures (SOPs), dedicated personnel, allocated funds, and specialized equipment for indirect contact. Routine socialization efforts were also lacking. Furthermore, the understanding of officers regarding the objectives, targets, and implementation of indirect contact, as well as their competence, played significant roles in the implementation. Conclusion: Implementing indirect contact services has not been optimal, necessitating increased support from BPJS Health Jambi Branch for improving indirect contact services